Habibi - Nye, Naomi Shihab (New York : Simon & Schuster Books for Young Readers, 1997)
When fourteen-year-old Liyanne Abboud, her younger brother, and her parents move from St. Louis to a new home between Jerusalem and the Palestinian village where her father was born, they face many changes and must deal with the tensions between Jews and Palestinians.
GR 6-8
Keywords: Families -- Israel -- Jerusalem -- Juvenile fiction; Emigration and immigration -- Juvenile fiction; Jewish-Arab relations -- Juvenile fiction; Jerusalem -- Juvenile fiction